Housing Affordability and Decarbonisation in Europe - Alejandro Fernández Pérez (A+BE: Architecture and the Built Environment)
Housing markets have produced structural inequalities evident in the unaffordability issues experienced by many households across Europe. Over the past century, housing has shifted from a domain of strong government intervention to one increasingly influenced by market forces. Today, as Europe decarbonises, not only affordability but also sustainability have become central to housing debates. This dissertation investigates how decarbonisation policies affect both housing affordability and provision. Following an essay-based structure (capita selecta), this thesis brings together studies on fiscal policy, sustainable finance, and social housing provision across various European settings. The dissertation is divided into two main parts. Part I, Affordability and Costs, employs quantitative methods to assess the economic impacts of decarbonisation on households. Part II, Provision and Finance, takes a qualitative approach to examine financing mechanisms for decarbonisation and social housing provision. While each part draws on distinct methodologies, together they provide an overview of how certain decarbonisation policies interact with housing systems at both household and structural levels. The findings show that current decarbonisation policies often favour wealthier homeowners through subsidies and tax incentives, while having a negative or mixed impact on renters, younger households, and low-income groups. To address these challenges, the thesis advocates for redistributive fiscal reforms—such as energy efficiency-linked property taxes—and stronger public institutions and regulations to guide investment towards equitable and sustainable housing provision. By placing affordability at the centre of decarbonisation policies, this dissertation aims to inform the development of transitional pathways that align both social and environmental goals.